The Real Value of CSR Performance in the NEV Industry: Evidence from China - Qing Wu; Theeralak Satjawathee (International Journal of Financial Studies)
Corporate social responsibility (CSR) is increasingly becoming a major concern for investors and consumers, prompting companies to devote more resources to community engagement to manage conflict and improve business performance. In this study, we conducted an empirical analysis with a sample of 385 listed companies in China’s new energy vehicle (NEV) industry to analyze the relationship between CSR performance and corporate value (CV). With the ordinary least squares (OLS) regression analysis, our study’s results show a positive relationship between the CSR performance of these companies and corporate value. In addition, our findings indicate a lagged effect in the relationship between CSR and CV. The mechanism analysis suggests that corporate CSR performance helps to improve corporate reputation, reduce financing constraints, and thus increase corporate value. Moreover, high analyst attention and information transparency can enhance the positive effects of corporate CSR. This study contributes to the existing literature and empirical evidence by exploring the correlation between CSR performance and firm value in the context of emerging countries and the NEV industry.